Structures Congress 2014 2014
DOI: 10.1061/9780784413357.104
|View full text |Cite
|
Sign up to set email alerts
|

Through-Thickness Thermal Behavior of Two RC Bearing Walls under Fire

Abstract: This paper discusses the through-thickness thermal behavior of two full-scale reinforced concrete (RC) bearing wall test specimens subjected to one-sided fire. The most probable fire exposure for RC wall structures is from one side of the wall only (i.e., compartment-type fire). This fire scenario causes steep thermal gradients through the wall thickness, leading to unsymmetrical fire damage and material degradation that can exacerbate out-of-plane eccentricity effects and compromise stability under service-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In terms of ultimate load, yield load, cracked load, stiffness and ductility, Go et al [4] concluded that reinforced lightweight aggregate concrete walls possessed better fire resistance and structural behavior than reinforced normal weight aggregate concrete walls under the same test conditions. Mueller and Kurama [5] compared the measured thermocouple data from walls with analytical predictions from a simulation software in order to predict the through-thickness thermal gradients with validity. The post-fire seismic behavior of concrete walls was investigated under the low frequency cyclic loading by Xiao et al [6] and Liu et al [7], revealing that the fire exposure deteriorated seismic behavior of walls.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of ultimate load, yield load, cracked load, stiffness and ductility, Go et al [4] concluded that reinforced lightweight aggregate concrete walls possessed better fire resistance and structural behavior than reinforced normal weight aggregate concrete walls under the same test conditions. Mueller and Kurama [5] compared the measured thermocouple data from walls with analytical predictions from a simulation software in order to predict the through-thickness thermal gradients with validity. The post-fire seismic behavior of concrete walls was investigated under the low frequency cyclic loading by Xiao et al [6] and Liu et al [7], revealing that the fire exposure deteriorated seismic behavior of walls.…”
Section: Introductionmentioning
confidence: 99%